Contact sensitization in metalworkers: Data from the information network of departments of dermatology (IVDK), 2010-2018 - Schubert, Steffen; Brans, Richard; Reich, Anna; Buhl, Timo; Skudlik, Christoph; Schröder-Kraft, Claudia; Gina, Michal; Weisshaar, Elke; Mahler, Vera; Dickel, Heinrich; Schön, Michael P.; John, Swen M.; et al. (Contact dermatitis, 2020)
Background Metalworkers are exposed to a variety of contact allergens by handling tools, metals, metalworking fluids (MWFs), oils and greases, rubber materials, and so on. Most large-scale reports on contact allergy due to MWFs are more than 10-years-old, and there are only few studies on contact allergy in mechanics and other metal workers not exposed to MWFs. Objectives To describe a current spectrum of contact sensitization in metalworkers with occupational dermatitis (OD). Patients and Methods Retrospective analysis of patch test data collected by the Information Network of Departments of Dermatology (IVDK; 2010-2018), stratifying for 804 cutting metalworkers, 2197 mechanics, and 355 other metalworkers. Results Cutting metalworkers were most frequently sensitized to monoethanolamine (12.6%), colophonium/abietic acid (11.4%) and formaldehyde releasers (up to 8.5%) from the MWF series, and formaldehyde (4.6%) and iodopropynyl butylcarbamate (4.6%) from the baseline series. Sensitization among mechanics and other metalworkers indicates possible occupational exposure to MWFs, glues, and resins, although this may not be expected from their job titles. Conclusions The spectrum of MWF contact allergens remained largely unchanged during the last years. Taking a comprehensive occupational history is indispensable in order to not miss relevant allergen exposures.
Gesehen am 04.03.2025